Self-determined motivation and subjective well- being in Portuguese veteran athletes in different sports. - Batista, Marco (2019)
With the increase of life expectancy associated to the need for a healthy lifestyle, there has been an increase in the number of persons involved in veterans' sports activities. The objective of this study was to evaluate the levels of self-determination for sports practice and subjective well-being in veteran athletes, depending on the different type of sports practiced. For data collection, the validated Portuguese versions of the Basic Psychological Needs Exercise Scale (BPNES), the Behaviour Regulation Sport Questionnaire (BRSQ), the Satisfaction with Life Scale (SWLS) and the Positive and Negative Affects Scale (PANAS) were used. The study sample consisted of 684 Portuguese veterans athletes of both genders, aged between 30 and 90 years (M = 43.78 SD = 8.61), of which 86.3% (590 individuals) of the male gender and 13,7% (94 individuals) of the female gender, mostly with 3 to 5 hours of training per week, with 19.5±12.2 years of practice, competitors in several individual sports (43%), team sports (37%) and individual and teams sports (20%). Veteran athletes are highly satisfied with basic psychological needs. When compared, athletes who practice individual sports and simultaneously individual and team sports differ significantly in the autonomous, controlled and amotivation compared to athletes who only practice team sports, as well as in positive and negative effects.